Riverbed Materials Crusher Plant Site Evaluation along Daraudi River in Gorkha District using Geographical Information System - Kumal, Prativa; Rakhal, Sunil; Malla, Pramesh (Journal of Sustainability and Environmental Management, 2024)
Selecting optimal locations for crusher plants is essential for promoting sustainable development and reducing environmental impact. This study applies Geographical Information Systems (GIS) to identify the restricted area for the location of a crusher plant along the Daraudi River in Nepal’s Gorkha District. This analysis aligns with national regulations and environmental guidelines, as outlined in the Stone Aggregate Crusher Guidelines Revised 2079, by integrating multiple criteria such as transportation access, proximity to settlements, historical and cultural sites, educational institutions, and environmental factors. A final map incorporating all the factors was developed, showing that almost 56% of the study area is not eligible for the establishment and operation of the crusher plant. In addition to this, it is also found that all the existing six Stone Aggregate Crusher plants do not comply with the national rules and regulations that must be monitored. The results demonstrate that GIS supports sustainable decision-making and compliance with local regulatory frameworks, thereby contributing to the development of responsible infrastructure.